Business Power and the Politics of Postneoliberalism: Relations Between Governments and Economic Elites in Bolivia and Ecuador. (June 2016) - Wolff, Jonas
ABSTRACT: The article analyzes and compares the dynamics of business‐government relations in Bolivia and Ecuador during the presidencies of Evo Morales and Rafael Correa. It specifically traces the shift from confrontation to rapprochement to a fairly stable pattern of negotiation and dialogue that characterizes the two governments' interaction with core business elites. Drawing on the structural and instrumental power framework developed by Tasha Fairfield, it proposes an explanation that accounts for this overall shift as well as for the main differences between the two countries. In a nutshell, the article argues that the business elites' response to a severe loss of instrumental power and the governments' response to the persistent structural power of business combined to cause the shift toward negotiation and dialogue. The article also probes the plausibility of this power‐based explanation by briefly comparing the two cases with other left‐of‐center governments in the region.